Citizenship and Health Care in Canada - Maioni, Antonia (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2010)
The link between citizenship and social policy occupies an important space in the development of postwar governance in Canada and elsewhere. And health care represents perhaps the most important example of the way in which government social programs can enhance citizenship and state legitimacy, and establish the boundaries of social consensus and mutual rights and responsibilities between citizens. The impact of social policies in promoting citizenship regimes and the tensions inherent in sustaining the commitments are evident in most modern welfare states. The case of Canada is one of the most intriguing.  This article looks in more detail at the anomalous combination of strong provincial governance that co-exists with a more centralized nation-building process in Canada. It explores the development of health care in Canada through the lens of the interface between federal and provincial governance and the kinds of challenges in decision-making that persist in health reform today.